2000
DOI: 10.1177/1077558700057002s08
|View full text |Cite
|
Sign up to set email alerts
|

Quality Measures for Mental Health Care: Results from a National Inventory

Abstract: The National Inventory of Mental Health Quality Measures was funded by the Agency for Healthcare Research and Quality to (1) inventory process measures for assessing the quality of mental health care; (2) identify clinical, administrative, and quality domains where measures have been developed; and (3) identify areas where further research and development is needed. Among the 86 measures identified, most evaluated treatment of major mental disorders, for example, schizophrenia (24 percent) and major depression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 15 publications
0
14
1
3
Order By: Relevance
“…A second limitation concerns the administrative indicators of quality of care, which are generally "less sensitive measures of health care processes than consumer derived indicators" (39) and often lack validation (40). For example, our criterion of three months to define early reregistration may be somewhat arbitrary.…”
Section: Discussionmentioning
confidence: 99%
“…A second limitation concerns the administrative indicators of quality of care, which are generally "less sensitive measures of health care processes than consumer derived indicators" (39) and often lack validation (40). For example, our criterion of three months to define early reregistration may be somewhat arbitrary.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the literature [1, 2, 30], the following variables were identified: Access to care: 1) ER use and frequency of ER use, 2) hospitalization and length of stay, 3) number of outpatient consultations for any reason during year of study among PMI using the ERs; and 4) consultations among PMI without ER use; 5) outpatient consultations within the week preceding an ER visit for any reason; and 6) outpatient consultations for the year prior to an ER visit for MH reasons. Continuity of care : 1–2) outpatient consultations for MH reasons within a week, or month, after an ER visit, or 3–4) hospitalization under the same conditions; 5) repeat ER visits for any reason within 30 days after a first visit to ERs, or after a hospitalization; and 6) hospitalization of patients who re-visited the ERs and reasons for re-visits (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Indicators used to assess MHS quality and impact on MH reforms include access, continuity and appropriateness of care [2, 30, 31], with ER attendance as a key indicator of health system access [32, 33]. Canadian and international studies have reported elevated rates of high (more than 4) and very high (more than 12) ER visits/year among PMI, particularly those with co-occurring MI and chronic physical illnesses or SUD [3436], as compared with other patients [3641].…”
Section: Introductionmentioning
confidence: 99%
“…Continuity of care is widely held to be beneficial for people with long‐term conditions, including SMI. It is valued by patients and providers and considered good practice in mental health and family medicine, reducing fragmentation of care and facilitating better provider‐patient relationships . Relational continuity—the longitudinal relationship between a patient and a health care practitioner (or group of practitioners)—is often the focus of efforts to improve continuity.…”
Section: Introductionmentioning
confidence: 99%